Pengaruh Pergaulan Teman Sebaya Tehadap Motivasi Belajar - Ardiansyah Ardiansyah (Educatio, 2022)
The purpose of this study was to determine how peer association affects motivation to study at the State University of Gorontalo.  The population in this study was all students who took the Introduction to Macroeconomics course in the odd semester of the 2020/2021 academic year at the Economics Education Study Program, Faculty of Economics, State University of Gorontalo.  We used a technique called "saturated sampling" in this study. In other words, sample all populations.  In this study, the independent variable is the association between peers and the dependent variable is students' learning motivation. The data analysis technique used is simple regression analysis.  The results of this study indicate that peer association has a positive effect on learning motivation.